Repair of damage in pipes using bonded GFRP patches. (15th September 2022) - Reis, J.M.L.; Costa, A.R.; da Costa Mattos, H.S.
Abstract: This work investigates the repair of corrosion damage in metallic pipes using glass fiber reinforced plastic (GFRP) patches. The main idea is to analysis of the effect of the thickness of the GFRP patch and the patch surface roughness on the effectiveness of the repair. Commonly, to perform such repair, a composite sleeve wrap is used according to international standards. The work shows that is not necessary a composite sleeve to repair low pressure leaking metallic pipes, only a bonded GFRP patch is sufficient. Burst tests were performed on API 5L gr.B steel hydrostatic specimens with a 10, 15 and 25 mm hole repaired with 100 mm X 100 mm GFRP patches with three different surface roughness. The effectiveness of the repair is strongly dependent on its thickness and surface roughness of GFRP patches. Experimental results show a relation with failure pressure GFRP patch thickness and surface roughness. Higher GFRP patch thickness, elevated failure pressures are presented. Also, high values of surface roughness produce increased failure pressures. A model based on the Linear Elastic Fracture Mechanics is used to obtain an estimate failure pressure using only one algebraic equation.